2022
DOI: 10.1039/d1cp04557a
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high permeable phenine nanotube membranes for water desalination

Abstract: Nanopore desalination technology hinges on high water-permeable membranes which, at the same time, block ions efficiently. In this study, we consider a recently synthesized [Science363, 151–155 (2019)] phenine nanotube...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
(123 reference statements)
0
3
0
Order By: Relevance
“…As some new nanotubes have been discovered, their desalting properties have also been studied. Naskar et al 35 used both EMD and NEMD simulations investigated the desalination performance of phenine nanotube (PNT) and found that it completely rejects salts, and permeates water at a rate which is an order of magnitude higher than that of all the membranes used for water filtration. MD simulations were conducted by Li et al 222 show that carbon nanocones (CNCs) can be used to water desalination, and the salt rejection and water flow of CNCs depends on the cone size, angle, and flow direction.…”
Section: Simulations For the Applications Of Nanofluidicsmentioning
confidence: 99%
See 1 more Smart Citation
“…As some new nanotubes have been discovered, their desalting properties have also been studied. Naskar et al 35 used both EMD and NEMD simulations investigated the desalination performance of phenine nanotube (PNT) and found that it completely rejects salts, and permeates water at a rate which is an order of magnitude higher than that of all the membranes used for water filtration. MD simulations were conducted by Li et al 222 show that carbon nanocones (CNCs) can be used to water desalination, and the salt rejection and water flow of CNCs depends on the cone size, angle, and flow direction.…”
Section: Simulations For the Applications Of Nanofluidicsmentioning
confidence: 99%
“…Such new flow phenomena of fluid occur within the nano-confinement channel bring out novel applications of nanofluidics and promote industrial innovation in many fields, include desalination, [32][33][34][35][36][37][38] energy harvesting, [39][40][41][42][43][44][45][46][47][48] nanofluidic iontronics, [49][50][51][52][53][54][55] gas separation, [56][57][58][59][60] heat exchanger, [61][62][63][64][65][66] biological analyses, 3,4,[67][68][69] and so on, as shown in Figure 1. The size of nanochannels is often a key factor affecting their applications.…”
Section: Introductionmentioning
confidence: 99%
“…Since their discovery, the phenine nanotubes have drawn the attention of material scientists and have been explored for a wide range of potential applications including photophysical, sensing, ionic transistors, molecular sieving, blue energy harvesting and luminescence [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%